2012
DOI: 10.3109/09638288.2012.709306
|View full text |Cite
|
Sign up to set email alerts
|

Reinvestigation of the dysfunction in neck and shoulder girdle muscles as the reason of cervicogenic headache among office workers

Abstract: Dysfunction of trapezius muscle was most responsible for CEH etiology. Proposed algorithm of kinesiotherapy was effective as complementary method of the CEH patients treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 44 publications
1
35
0
Order By: Relevance
“…3,4 Mean value of mcEMG amplitude recorded from abductor pollicis brevis muscle discriminated patients well. sEMG frequency index does not present the diagnostic value, previous studies described mainly abnormal activity of neck and shoulder girdle muscles.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…3,4 Mean value of mcEMG amplitude recorded from abductor pollicis brevis muscle discriminated patients well. sEMG frequency index does not present the diagnostic value, previous studies described mainly abnormal activity of neck and shoulder girdle muscles.…”
Section: Discussionmentioning
confidence: 99%
“…24 sEMG recordings from sternocleidomastoid, trapezius, biceps brachii and abductor pollicis brevis muscles were bilaterally performed both at rest (rEMG) and during their maximal contraction (mcEMG) lasting 5 seconds. 3,4,23,25 The parameters of average amplitude and frequency index were analyzed. The frequency index from 5 to 1 (5 ->95Hz, 4 -95-70Hz, 3 -65-40Hz, 2 -35-10Hz, 1 -<10Hz) evaluated the recruitment pattern of motor units action potentials.…”
Section: Patients and Study Designmentioning
confidence: 99%
See 2 more Smart Citations
“…(29) Trigger points have been identi ed in those with CGH in the upper trapezius, SCM, erector spinae, and suboccipital muscles. (27,30) Trigger points of the SCM can produce a unilateral referred pain over the forehead and around the ipsilateral eye and ear as seen in CGH. (31) It has been demonstrated that CGH is caused by dysfunction of the upper cervical spine.…”
Section: Introductionmentioning
confidence: 99%